Accessibility Adaptation in the Design of Heritage Boutique Hotels: Malacca case studies - Abdul Kadir, Syazwani; Jamaludin, Mariam; Awang, Abd Rahim (Environment-Behaviour Proceedings Journal, 2020)
This paper undertakes a study on accessibility adaptation in the design of heritage boutique hotels in Malacca. Three heritage boutique hotels located in Malacca City were selected as the case studies. The objective is to explore the heritage boutique hotels’ methods of adapting accessibility in their hotel design. Research methodology employed is observation, which include site observation and photo documentation. Data from the observation were analyzed and discussed qualitatively. Findings indicate that all three case studies were designed with users’ accessibility in mind in spite of the challenge in carefully preserving the buildings’ heritage value. Keywords: Accessibility adaptation; Heritage building; Hotel design; Boutique hotel eISSN: 2398-4287 © 2020. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v5i13.2094